Construction Management Analysis of the Cimunjul Bridge Development on the Bogor – Ciawi – Sukabumi Toll Road (Bocimi) Section 3 - Ade Yusrizal Ula; Fujiyanto Fujiyanto; M. Hildan Rafsanjani; Heri Mulyono; Ohan Farhan (Pusat Publikasi Nusantara, 2026)
This study analyzes time and cost management in the construction of the Cimunjul Bridge on the Bogor-Ciawi-Sukabumi (Bocimi) Toll Road Section 3 with the dimensions of the bridge, which is 254,663 meters long and 32.4 meters wide. The purpose of building the Cimunjul bridge on the Bocimi Toll Road section 3 is to connect Parungkuda – West Sukabumi. The purpose of the research is to plan Time and Cost management based on the Analysis of Work Unit Prices (AHSP) of Cirebon Regency Highways in 2025 and to determine what are the factors that affect time and cost efficiency in the construction of the Cimunjul Bridge on the Bogor – Ciawi - Sukabumi (Bocimi) Toll Road Section 3. The method used is a quantitative approach with primary data from the Project and field observations. The results of the study show that the calculation from the Cimunjul Bridge Cost Budget Plan (RAB) using the Cirebon Regency Highway Highway Work Unit Price Analysis (AHSP) in 2025 is worth IDR 190,985,225,558.80 with a work time of 183 days. Work delays are generally caused by resource constraints and weather factors, while cost efficiency can be achieved through strict time control using the Critical Path Method (CPM) method.